President's Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2017)
I can’t believe how quickly time passes. My term as ORNAC President will be coming to an end in just a few months. It has, so far, been an extremely busy and exciting term. When I took office as ORNAC President I had goals and objectives that I wanted to achieve. This included addressing priorities within the ORNAC strategic plan. These were not just my priorities. They were the priorities of many, if not all, ORNAC members as perioperative colleagues.